Evaluation of alternative land-use scenarios using an ecosystem services-based strategic environmental assessment approach. (September 2021) - Nijhum, Farzana; Westbrook, Cherie; Noble, Bram; Belcher, Ken; Lloyd-Smith, Patrick
Abstract: Ecosystem services valuation is not new, but few approaches have been developed to support ecosystem service consideration at the strategic level of futures-based planning. This paper demonstrates a practical, strategic environmental assessment approach to incorporate the valuation of ecosystem services in a futures-based assessment to support land use planning decisions for urban ecological areas. The application is based on the Northeast Swale, a valued natural area consisting of prairie grasslands and ephemeral wetlands in Saskatoon, Saskatchewan, Canada, which is subject to the cumulative pressures of urban development. Land use attributes or end points are adopted as proxies for ecosystem services to simplify the complexity of ecosystem services and to ensure outcomes that are practical and relevant to those who make land use decisions. The value of land use attributes is assessed using a choice experiment that incorporates visual interpretations of alternative land use futures, from which residents' marginal willingness to pay for attributes are determined. Using compensating surplus values, tradeoffs between alternative future scenarios are explored and a range of preferred land use futures identified that depict different land use attributes and thus the suite of benefits residents derive from ecosystem services. Lessons are discussed for improved integration of ecosystem services valuation in strategic land use planning, and for translating complex ecosystem service concepts into practical directions for urban residents and for those responsible for land use policy and planning decisions. Highlights: Understanding ecosystem services values can inform land use decisions. A practical approach is presented to assess ecosystem services in land use planning. Scenario analysis allows for 'what if' valuation of ecosystem services. Land use attributes or end points simplify ecosystem services for decision makers. SEA is a valuable tool for ecosystem services-based land use decisions.